Narrativas, “espaço” e dádivas. A conformação de um Movimento de luta por moradia - Bologna, Paula Cristina Corrêa (2018)
The reflections presented in this work are the result of two years of ethnographic research realized with the Movimento de Moradia da Região Centro (MMRC) or the Housing Movement of the Centre Region. The MMRC is a social movement compound for low-income families, which claim for the right of decent houses in the city centre of São Paulo, thought their insertion in public policy programmes. The problematic of the lack of decent housing for low-income populations is the background of this work, but it is not on this specific issue that its treats. This work is about the multiple relations which produce a housing social movement, the above mentioned MMRC. To approach such relations, I have highlighted three aspects: i) the use of narratives of the leadership trajectories, and how these narratives are mobilised to build connections between militants and Movement, as much as the narratives are also feeding for political and life resistance to the militants. ii) The relations of the everyday in the Mauá Occupation show that the term "space" used by them to name the place of dwelling within the Occupation, cannot be assumed as a synonym for “house.” On the contrary, “space” is a term that has its own meaning and temporality, as well as being a locus to produce other sociabilities for occupants. iii) The exchange regime in which the relations between the MMRC and the São Paulo City Hall are established, can also be understood as mediated by mechanisms of gifts, including those of the agonistic type.